1941
DOI: 10.1111/j.1151-2916.1941.tb15443.x
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Zirconia in Soda‐borosilicate Glasses*

Abstract: Titanium Alloy Manufacturing Company for their helpful suggestions throughout the course of this work. They also wish to thank B. D. Bruce, ceramic engineering student the enamels. This investigation was financed by the Titanium Alloy Manufacturing Company of Niagara Falls, N. Y., and was conducted as a cooperative project in the Department of Ceramic Engineering under the auspices of the Engineering Experiment Station at the University of Illinois. ~~~~~~~~~o RNGINEERINC IJRBANA, ILLINOISType I1 enamels shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The compositional dependence on ZrO 2 solubility has been reported by various authors [10][11][12][13][14][15] and there appears to be an additive effect. The information can be presented as 4 principles: It has been shown that change in solubility of ZrO 2 varies in a fixed stoichiometry with the number of alkali ions in excess of that needed to charge compensate aluminium 1 [15,16].…”
Section: Introductionmentioning
confidence: 83%
“…The compositional dependence on ZrO 2 solubility has been reported by various authors [10][11][12][13][14][15] and there appears to be an additive effect. The information can be presented as 4 principles: It has been shown that change in solubility of ZrO 2 varies in a fixed stoichiometry with the number of alkali ions in excess of that needed to charge compensate aluminium 1 [15,16].…”
Section: Introductionmentioning
confidence: 83%
“…The chemical bonding principles between a veneer layer and a metal substrate have only a limited significance and transferability to the bonding mechanisms in veneered zirconia restorations. Early research on the interface between zirconia and borosilicate glasses showed a certain solubility of zirconia in the glass at elevated temperatures of 815 or 1200 • C [50]. It has also been shown that zirconia enters the glass network as six-or eight-coordinated network modifiers [51].…”
Section: The Zirconia-veneer Interfacementioning
confidence: 99%
“…For new D‐Glass fibers, both alkaline earth oxides and alumina have been introduced at the expense of SiO 2 or B 2 O 3 or both In turn, microscale phase separation of the traditional D‐glass has been suppressed during fiber drawing. In designing AR‐Glass compositions a common, key feature is that nearly all of Al 2 O 3 has been replaced by ZrO 2 …”
Section: Fiber Glass Compositionsmentioning
confidence: 99%
“…In designing AR-Glass compositions a common, key feature is that nearly all of Al 2 O 3 has been replaced by ZrO 2 . [9][10][11] Compositions of the above specific mixtures drive the changes of glass properties, such as density, viscosity, liquidus temperature, chemical durability, mechanical property, dielectric property, thermal property, etc. As an example, Figure 1 depicts the measured composition effects on T F and fiber Young's modulus, respectively, for E-Glass-based compositions.…”
Section: Fiber Glass Compositionsmentioning
confidence: 99%